2004
DOI: 10.1080/13682820410001681207
|View full text |Cite
|
Sign up to set email alerts
|

Verbal deficits in Down's syndrome and specific language impairment: a comparison

Abstract: Future research should consider whether similarities in the language behaviours associated with Down's syndrome and specific language impairment could be related to similarities at other levels of analysis, including neurological development and genetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 187 publications
(202 reference statements)
6
47
0
5
Order By: Relevance
“…DS is associated with moderate to severe cognitive impairment with IQs in the range of 30 to 70 (Chapman & Hesketh, 2000;Glenn & Cunningham, 2005). Most individuals have language difficulties but there is wide variation in the severity of impairments and a characteristic profile of strengths and weaknesses with receptive vocabulary widely recognised as a developmental strength (e.g., Abbeduto, Warren, & Conners, 2007;Chapman, 1997;Chapman & Hesketh, 2000;Fowler, 1995;Gunn & Crombie, 1996;Laws & Bishop, 2004;Martin, Klusek, Estigarribia, & Roberts, 2009;Roberts, Price, & Malkin, 2007;Rondal, 1995;Rosin, Swift, Bless, & Vetter, 1988;Tager-Flusberg, 1999;Vicari, Caselli, & Tonucci, 2000;Ypsilanti & Grouios, 2008).…”
Section: Individuals With Down Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…DS is associated with moderate to severe cognitive impairment with IQs in the range of 30 to 70 (Chapman & Hesketh, 2000;Glenn & Cunningham, 2005). Most individuals have language difficulties but there is wide variation in the severity of impairments and a characteristic profile of strengths and weaknesses with receptive vocabulary widely recognised as a developmental strength (e.g., Abbeduto, Warren, & Conners, 2007;Chapman, 1997;Chapman & Hesketh, 2000;Fowler, 1995;Gunn & Crombie, 1996;Laws & Bishop, 2004;Martin, Klusek, Estigarribia, & Roberts, 2009;Roberts, Price, & Malkin, 2007;Rondal, 1995;Rosin, Swift, Bless, & Vetter, 1988;Tager-Flusberg, 1999;Vicari, Caselli, & Tonucci, 2000;Ypsilanti & Grouios, 2008).…”
Section: Individuals With Down Syndromementioning
confidence: 99%
“…A direct comparison of language abilities in DS and typical SLI, based on scores indexed by nonverbal MA and standardized relative to the scores of MA-matched typically developing children, showed similar profiles of strengths and weaknesses (Laws & Bishop, 2003). Despite the agreement among reviewers on the relative strength in semantic knowledge indexed by vocabulary breadth (e.g., Abbeduto, et al, 2007;Laws & Bishop, 2004), there has been little interest in understanding whether this is commensurate with vocabulary depth, possibly because of assessment difficulties.…”
Section: Vocabulary and Semantic Knowledge In Sli And Down Syndromementioning
confidence: 99%
“…This difficulty with compiling accurate phonological representations could in turn lead to both the inconsistency observed in speech production, and a pattern of better repetition than naming skills. Indeed, recent evidence has shown that DS children's verbal short term memory skills are related to their speech production (Laws, 2004).…”
Section: Speech Production In Children Wih Ds /mentioning
confidence: 99%
“…In particular, most studies report that children with Down syndrome show relative strengths in the development of joint attention behaviors, or the use of eye contact, gesture, and vocalization for the purposes of nonverbal social sharing [Mundy et al, 1988Mundy et al, 1995;Fidler et al, 2005]. By the time children with Down syndrome arc verbal, pragmatics have been suggested to be an area of relative strength [Johnston and Stansfield, 1997;Laws and Bishop, 2004]. In addition, the use of nonverbal communication to initiate or request social contact seems to develop in mental age appropriate ways as well [Fidler et al, 2005].…”
Section: Features Down Syndromementioning
confidence: 99%